POTENSI INTERNET OF THINGS (IoT) UNTUK MASA DEPAN PERKOTAAN CERDAS (SMART CITIES) - Zulkarnain, S.Kom., M.MSI.; Arman (Journal of Information System and Technology (JOINT), 2025)
The IoT has the potential to revolutionize smart city growth by using live data to boost efficiency, improveresidents' well-being, and support ecological sustainability. This research explores how IoT is used in importanturban areas such as transportation, energy management, environmental monitoring, and public safety. Referringto current literature and real-world cases, the study demonstrates how IoT can offer creative answers to tackle theintricate issues encountered by contemporary urban areas. However, substantial obstacles persist, includingsecurity threats and the necessity for substantial financial resources. This research is intended to act as afundamental guide for researchers and professionals who want to delve deeper into the potential of IoT indeveloping intelligent, more sustainable city settings.Keywords: IoT, Smart City, Intelligent Transportation, Sustainability, Data Security